Long-Term Passive Sampler Monitoring of NO2 and SO2 for Trend Analysis and Control Strategies in South Sumatra - Vera Surtia Bachtiar; Ayu Arnita Putri; Yenni Yenni (Universitas Andalas, 2026)
Air pollution is one of the most pressing environmental issues, with direct impacts on human health and environmental quality. The increasing intensity of transportation activities, industrial operations, forest and land fires, and regional development in South Sumatra Province has increased the risk of air pollution, particularly from nitrogen dioxide (NO2) and sulfur dioxide (SO2). This study aims to analyze the concentrations and multi-year trends of NO2 and SO2 in South Sumatra based on passive sampler measurements conducted at 68 monitoring sites across 17 districts and municipalities during the period 2021–2024. The results show that the average concentrations of NO2 ranged from 6.654 to 9.944 micrograms per cubic meter, while SO2 concentrations ranged from 7.303 to 8.456 micrograms per cubic meter. All measured concentrations were below the National Ambient Air Quality Standards as well as the European Union guideline values. Trend analysis indicates a consistent decrease in NO2 and SO2 concentrations from 2021 to 2024. These findings contribute to the availability of long-term air quality data and enhance understanding of NO2 and SO2 dynamics, providing a scientific basis for the development of evidence-based strategies for air pollution control and prevention in South Sumatra Province. Keywords: nitrogen dioxide, sulfur dioxide, passive sampler, South Sumatra, air pollution trends.